Morfoloģiskie varianti normalizācijas vēstures aspektā - Druviete, Ina (Baltistica, 1989)
MORPHOLOGICAL VARIABILITY IN THE HISTORY OF STANDARDIZATION OF LANGUAGEThe stable norms of morphological elements are formed in the contemporary Latvian literary language, though there exist parallel variants and new variants of words appear.The standardization of language tends mainly to reduce morphological variability by determinating the semantical or stylistical shades of variants. It is necessary to analyse the main tendencies which regulate the dynamics of variability in different periods of literary language development. We must take into account the national tendencies of variability development, as well as the influence of certain scholars and most well-known sources of codificated norms who played the greatest part in the changing of norms.In order to codify any variant we can study the grammatical system of the language in its historical development, the history of competing variants, the frequency of using them in fiction in different periods, and the history of codification. The analysis of experience of previous linguists may facilitate the codification of morphological variants in contemporary literary language.